1994
DOI: 10.1007/bf00154307
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of production medium for ?-1,3-glucanase synthesis by Trichoderma harzianum

Abstract: Response surface methods were used to determine the optimum concentration of medium nutrients for extracellular p-1,3-glucanase production by Trichoderma harzianum in shakeflask culture. A Plackett-Burman design was used to screen the important variables which were then grouped and studied by a central composite design. The optimum levels of the medium constituents were determined by the complex algorithm of Box.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is observed that a maximal b-1,3-glucanase production of 0.820 U was obtained for initial glucose concentration of 8.63 g/dm 3 using the recommended medium [10]. The production of the enzyme decreased thereafter and no b-1,3-glucanase production was detected after an initial glucose concentration of 40 g/dm 3 .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…It is observed that a maximal b-1,3-glucanase production of 0.820 U was obtained for initial glucose concentration of 8.63 g/dm 3 using the recommended medium [10]. The production of the enzyme decreased thereafter and no b-1,3-glucanase production was detected after an initial glucose concentration of 40 g/dm 3 .…”
Section: Resultsmentioning
confidence: 91%
“…Our earlier communication elsewhere [10] dealt with the optimization of the medium constituents for maximum b-1,3-glucanase production by Trichoderma harzianum employing response surface methodology. In the present study, the effect of initial glucose concentration and b-1,3-glucanase production by Trichoderma harzianum NCIM 1185 and cell growth were investigated in a batch stirred tank bioreactor.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 2 more Smart Citations